Clinical Determinants and Prognostic Implications of Right Ventricular Dysfunction in Pulmonary Hypertension Caused by Chronic Lung Disease. Issue 2 (22nd January 2019) - Prins, Kurt W.; Rose, Lauren; Archer, Stephen L.; Pritzker, Marc; Weir, E. Kenneth; Olson, Matthew D.; Thenappan, Thenappan
Abstract : Background: Patients with pulmonary hypertension caused by chronic lung disease (Group 3 PH) have disproportionate right ventricle (RV) dysfunction, but the correlates and clinical implications of RV dysfunction in Group 3 PH are not well defined. Methods and Results: We performed a cohort study of 147 Group 3 PH patients evaluated at the University of Minnesota. RV systolic function was quantified using right ventricular fractional area change (RVFAC) and + dP/dtmax /instantaneous pressure. Tau and RV diastolic stiffness characterized RV diastolic function. Multivariate linear regression was used to define correlates of RVFAC. Kaplan‐Meier and Cox proportional hazards analyses were used to examine freedom from heart failure hospitalization and death. Positive correlates of RVFAC on univariate analysis were pulmonary arterial compliance, cardiac index, and left ventricular diastolic dimension. Conversely, male sex, N‐terminal pro‐brain natriuretic peptide, heart rate, right atrial enlargement, mean pulmonary arterial pressure, and pulmonary vascular resistance were negative correlates. Male sex was the strongest predictor of lower RVFAC, after adjusting for pulmonary vascular resistance and pulmonary arterial compliance. When comparing sexes, males had lower RVFAC (26% versus 31%, P =0.03) both overall and for any given mean pulmonary arterial pressure and pulmonary vascular resistance value. Males exhibited a reduction in + dP/dtmax /instantaneous pressure as pulmonary vascular resistance increased, whereas females did not. There were no sex differences in RV diastolic function. RV dysfunction (RVFAC <28%) was associated with increased risk of heart failure hospitalization or death (hazard ratio: 1.84, 95% CI: 1.04–3.10, P =0.035). Conclusions: Male sex is associated with RV dysfunction in Group 3 PH, even after adjusting for RV afterload. RV dysfunction (RVFAC <28%) identifies Group 3 PH patients at risk for poor outcomes.